2021
DOI: 10.1161/circ.144.suppl_1.12214
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 12214: Characterization of Iatrogenic Left Bundle Branch Block After Septal Myectomy for Hypertrophic Cardiomyopathy

Abstract: Introduction: LBBB results in impaired transseptal conduction and delayed posterolateral LV activation. Criteria for left bundle branch block (LBBB) vary across scientific organizations. Septal myectomy for hypertrophic cardiomyopathy (HCM) could serve as an iatrogenic anatomic model to characterize LBBB. Objective: To describe ECG features of LBBB after septal myectomy for HCM. Methods: ECG data were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Likewise, in another recently published study on 2482 patients with obstructive HCM who underwent myomectomy, around 38.8% of patients developed LBBB, but did not incrementally influence their outcome [8]. In addition, Gionfriddo et al have shown that after extensive septal myomectomy, the QRS duration significantly increased from 94 ms ± 10 ms to 152 ms ± 15 ms, along with LV end-diastolic diameter (from 40 ms ± 5.6 ms to 46.2 ms ± 6.5 ms) at two months after the procedures [57]. Although things are just at the beginning, CRT and other biventricular pacing methods might become useful in these patients.…”
Section: Electrical Parameters In Stratifying Patients With Hcm For Crtmentioning
confidence: 98%
“…Likewise, in another recently published study on 2482 patients with obstructive HCM who underwent myomectomy, around 38.8% of patients developed LBBB, but did not incrementally influence their outcome [8]. In addition, Gionfriddo et al have shown that after extensive septal myomectomy, the QRS duration significantly increased from 94 ms ± 10 ms to 152 ms ± 15 ms, along with LV end-diastolic diameter (from 40 ms ± 5.6 ms to 46.2 ms ± 6.5 ms) at two months after the procedures [57]. Although things are just at the beginning, CRT and other biventricular pacing methods might become useful in these patients.…”
Section: Electrical Parameters In Stratifying Patients With Hcm For Crtmentioning
confidence: 98%